Children's participation from the perspective of teachers - Tuğçe Akyol; Havva Erdem (Journal of Pedagogical Research, 2021)
The perception of a teacher with regards to a child's participation and their practices affect his/her participation in educational institutions. To provide effective participation, teacher's awareness and attitudes towards participation must be examined. This research aims to determine the views of Turkish pre-school and elementary teachers on children's participation in educational institutions. The participants of the study were comprised of 16 teachers employed in public preschools and elementary schools in a province in Turkey's Inner Aegean Region. The teachers' interview form is used as the data collection tool in this study. As a result of the research, it was determined that teachers had a positive perspective on children's participation, they allow for certain conditions to enable participation coupled with decision-making processes in a limited fashion. Furthermore, it was concluded that teachers had methodical difficulties in decision-making and they thought that they needed to improve themselves in promoting participation. Teachers also thought that the teacher, peer relations, and family are effective on the participation.